Komunikasi Badan Narkotika Nasional Sumatera Barat dalam Implementasi Program Intervensi Berbasis Masyarakat (IBM) - Adri Yanto; Emeraldy Chatra; Ernita Arif (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This research examines the problem of narcotics which has become a global issue and a concern and has become an agenda in many countries and the international community. One of the attentions given by BNN is through the Community-Based Intervention Program (IBM). The Community-Based Intervention Program (IBM) is a rehabilitation for drug abusers designed from the community, for the community and by the community through recovery agents (AP) by utilizing community facilities and potential in accordance with local wisdom. This study aims to analyze the West Sumatra BNNP communication process and analyze BNNP communication barriers in running the IBM Program. The method used in this study is a qualitative method with in-depth interview techniques, observation and documentation. The results of this research are that the West Sumatra BNNP has a persuasive communication process, Lapau as a place to transfer information, Recovery Agents in embracing drug abusers and BNNP in collaboration with various stakeholders.